Performance analysis for distributed and parallel Java programs with Aksum - Seragiotto, C.; Fahringer, T. (2005 IEEE International Symposium on Cluster Computing and the Grid : May 9-12, 2005, Cardiff, Wales, 2005)
This paper deals with the challenging problem of performance analysis for Java programs. We describe procedures and requirements for instrumenting, monitoring, and analyzing distributed Java codes, and introduces Aksum, a highly customizable and flexible system for performance analysis that helps programmers to semi-automatically locate and understand performance problems in parallel and distributed Java programs. We also describe a sophisticated agent architecture as part of Aksum for static and dynamic instrumentation of Java programs. Experiments are presented for a widely distributed application running on a heterogeneous set of machines with different operating systems to illustrate the usefulness of our approach.